1995
DOI: 10.1172/jci117857
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by vascular endothelial growth factor of human colon cancer tumorigenesis in a mouse model of experimental liver metastasis.

Abstract: 1995.95:1789-1797.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
280
1
7

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(297 citation statements)
references
References 38 publications
9
280
1
7
Order By: Relevance
“…Studies from our laboratory and others suggest that VEGF is the angiogenic factor that is most closely associated with induction and maintenance of the neovasculature in human colon cancer (Warren et al, 1995;Ellis et al, 1996;Takahashi et al, 1996). Our present results show that treatment of mice with EGCG resulted in marked inhibition of the growth, vascularity, and proliferation of human tumour xenografts in nude mice.…”
Section: Discussionsupporting
confidence: 67%
“…Studies from our laboratory and others suggest that VEGF is the angiogenic factor that is most closely associated with induction and maintenance of the neovasculature in human colon cancer (Warren et al, 1995;Ellis et al, 1996;Takahashi et al, 1996). Our present results show that treatment of mice with EGCG resulted in marked inhibition of the growth, vascularity, and proliferation of human tumour xenografts in nude mice.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies have revealed that TAMs are a very critical cell group in tumor tissue and that TAMs contribute greatly to tumorigenesis and the protection of tumors from therapy (McDonnell et al, 2003). VEGF inhibition represses tumor angiogenesis, and this result has led to the clinical utilization of VEGF inhibitors to treat cancer (Warren et al, 1995;Presta et al, 1997). In our present study, we used a microvesicledelivered antagonucleotide against miR-150 to treat tumors.…”
Section: Microvesicle-delivered Mir-150 Inhibitor Prevents Tumorigenesismentioning
confidence: 99%
“…Inhibition of VEGF protein with neutralising antibodies will decrease the rate of growth of liver metastasis from colon cancer in an animal model. 11 A greater understanding of the role of VEGF in the prostate may lead to potential therapeutic strategies for both benign and malignant disease. The aim of our study was to evaluate the level of VEGF expression with the aid of immunocytochemistry in specimens of prostate cancer and BPH.…”
Section: Introductionmentioning
confidence: 99%